Effects of Cryoprotectant on Thermal Expansion of Articular Cartilage during Freezing Process - Yu Huaxing; Li Daixi; Xu Yi; Liu Li; Zhai Zhen; Zhang Yan (Zhileng xuebao)
Low-temperature fracture is often observed during the low-temperature preservation of articular cartilage. However，the biomechanical damaging mechanism of cryopreservation is still unclear. During freezing from 0 ℃ to -60 ℃，Thermol Mechanical Analysis (TMA) was used to investigate the effects of 4 kinds of cryoprotecants with different concentrations. The results indicate that: (1) the cartilage produced a great thermal stress due to the extracellular thermal expansion during the cooling process；(2) when adding a higher concentration of ethanol and glycol，the faster the cooling rate，the greater thermal stress the articular cartilage will produce，and thus，slower cooling rate is more suitable for the cryopreservation of articular cartilage；(3) while adding 1, 2 - propylene and glycerin，there is an optimal cooling rate (30C/min) and it produces cartilage a minimal thermal stress. Moreover，cryoprotectants of higher methylation will contribute better protective effect to the thermal expansion among the 4 kinds of alcohols.